ANALISIS KEBIJAKAN PERENCANAAN KEBUTUHANGURU SMA DI KABUPATEN ACEH TENGAH - Fauzan Isma, Murniati AR2, Niswanto (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2017)
ABSTRACT: The planning of teacher demand is a process to determine the number of teachers needed in order to fulfill the demand and balance the teacher demand and supply. This study aimed to describe the growing number of senior high school students and teachers needed in the process of teaching and learning the academic year of 2017/2018 to 2021/2022 inAceh Tengah Regency. This study used descriptive method with qualitative approach, and the data collection was conducted by the techniques of observation, interview, and documentation study and data analysis of reduction, display, and verification. To guarantee the validity of data, it was conducted credibility test with triangulation technique. The subjects of study were Education Department and Education and Training Employment Board ofAceh Tengah Regency. The results of the study showed that: (1) the highest enrolment of students for the last five years from 2011/2012 to 2015/2016 was in the academic year of 2014/2015 with the total of 5,067 students and the lowest enrolment was in the academic year of 2015.2016 with 4,903 students. (2) The teacher supply based on the 2013 curriculum was 402 teachers. (3) The projection result showed the senior high school teacher demand in Aceh TengahRegency for the academic year of 2017/2018 (558 teachers), 2018/2019 (556 teachers), 2019/2020 (530 teachers), 2020/2021 (554 teachers), and 2021/2022 (606 teachers), the demand has been included the number of teachers that would be retired.KEYWORDS: policy, planning, and teacher demam ABSTRAK: Perencanaan kebutuhan guru adalah proses untuk menentukan jumlah guru yang dibutuhkan agar tenaga guru dapat terpenuhi dan seimbang antara permintaan (demand) dan persediaan (supplay) guru. Penelitian ini bertujuan mendiskripsikan jumlah pertumbuhan Siswa SMA dan kebutuhan guru yang akan mengikuti proses belajar mengajar pada tahun ajaran 2017/2018 s/d 2021/2022 di Kabupaten Aceh Tengah. Penelitian ini menggunakan metode deskriftif dengan pendektan kualitatif serta pengumpulan datanya dilakukan dengan teknik observasi, wawancara dan studi dokumentasi serta analisis data dilakukan dengan reduksi, display dan verifikasi. Untuk menjamin keabsahan data dilakukan dengan uji kredibilitas dengan teknik triangulasi sumber data. Subjek penelitianya yaitu Dinas Pendidikan dan Badan Kepegawaian Pendidikan dan Pelatihan Kabupaten Aceh Tengah. Hasil penelitian ini menunjukkan bahwa: 1). Keadaan siswa 5 Tahun terakhir 2011/2012 s/d 2015/2016 enrolment paling tinggi pada tahun ajaran 2014/2015 berjumlah 5.067 orang dan terendah pada tahun 2015/2016 dengan jumlah 4.903 orang, 2) persediaan guru saat ini berdasarkan kurikulum 2013 berjumlah 402 orang, 3). Hasil proyeksi menunjukkan kebutuhan guru SMA di Kabupaten Aceh Tengah pada tahun ajaran 2017/2018 (558 orang), 2018/2019 (556 orang), 2019/2020 (530 orang), 2020/2021 (554 orang) dan 2021/2021 (606 orang) kebutuhan tersebut sudah termasuk dengan guru yang akan pensiun.KATA KUNCI : kebijakan, perencanaan, dan kebutuhan guru